PEMANFAATAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN KREATIVITAS BELAJAR SISWA SEKOLAH DASAR - Ikhsan Maulana; Ahmad; Hermansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyse the use of animated videos in enhancing the learning creativity of primary school students. Using qualitative methods and a field study approach through observation, interviews, and document analysis of teachers and students in Grade IV at Rato State Primary School, it was found that animated videos are able to attract interest in learning, clarify understanding, and encourage students' imagination and creative ideas. Creativity is evident through original thinking, courage to experiment, and the creation of simple works. Success is influenced by teacher planning, selection of relevant content, and activities that stimulate creative thinking. It is concluded that animated videos have great potential as an innovative learning strategy. Further research is recommended using a quantitative approach and the development of interactive video models across subjects.